Fiscal competition and a potential growth effect of centralization - Kersten Kellermann (Universität Liechtenstein, Konjunkturforschungsstelle Liechtenstein (KOFL), 2007)
I discuss a dynamic version of the Zodrow-Miezskowski model, where world capital supply is not fixed. The time horizon of the welfare maximizing government is assumed to be infinite whereas the household sector is designed according to the two-period overlapping-generations model. Thus social evaluation is involved which is not directly based on individual preference ordering. The model produces a type of inefficiency caused by a head tax on immobile workers. From the viewpoint of the global economy, head taxes reduce global saving and thus create a negative externality on global capital supply. The lower-level government thus financed the public goods supply with too little reliance on source taxes. In this case, centralization of investment decisions has the potential of welfare improvement. It can lead to an increase in private and public investment and enhances transitory growth
Keywords: H70; H10; 330; Public investment; Tax competition; Fiscal competition; Social time preference; Federalism; Steuerwettbewerb; Kapitalmobilität; Dezentralisierung; Investition; Overlapping Generations; Wachstumstheorie; Theorie